Maine’s Journey into the Arctic: Why the Arctic Council Matters to Maine - Canarie, Dave (Maine Policy Review, 2016)
High-level Arctic officials from the United States and seven other nations in the Arctic region, and representatives of indigenous people from the Arctic, gathered in Portland October 4–6, 2016, to discuss issues of importance to the region. In this commentary, Dave Canarie describes what the Arctic Council is and why it matters to Maine.